Job Creation and Job Destruction in EU Agriculture - Liesbeth Dries; Pavel Ciaian; d'Artis Kancs (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
This is the first paper to study job creation and destruction in EU agriculture. We disaggregate gross employment patterns and net job flows into detailed intra-sectoral labour adjustment dynamics based on a unique EU-wide firm level panel dataset for 1990-2005. We find that: (1) job creation and destruction rates in EU agriculture are comparable to other sectors; (2) there is some evidence of ongoing substitution of family labour for hired labour (3) there are important differences in job creation and destruction rates between different Member States; (4) these differences can be attributed to structural differences across countries, sectors and firm types; (5) time variation of job reallocation fluctuates countercyclically; (6) idiosyncratic effects are the main driver of time variance in job reallocation.
Keywords: 330; Job creation; job destruction; FADN; EU; labour adjustment in agriculture; Beschäftigung; Arbeitsmobilität; Landwirtschaft; EU-Staaten